(untitled) (TAJ: Journal of Teachers Association, 2010)
Objective To asses the results are reducing and maintaining intraocular pressure of a patient having cataract with glaucoma, Performing Trabeculectomy (Filtration Surgery) and small incision cataract surgery (SICS) by the same wound & same sitting. Method and Materials This study was done at Rajshahi Medical College Hospital from July 2006 to June 2008. Forty (40) patients of age ranging from 45 to 65 years were selected randomly having cataract with glaucoma. Intraocular pressures (IOP) were 14mmHg to 17 mmHg preoperatively with anti-glaucoma medication. Visual acuity of all patients was perception of light to counting finger (CF) half meter to one meter. Thirty eight (38) patients (95%) had open angle glaucoma and two patients had chronic angle closure glaucoma. Informed consent was taken from all the patients. Trabeculectomy were done in the SICS wound. Side ports were made in every case. Delivery of nucleus, washing of cortical matter and introduction of PCIOL all are done under local anesthesia. Results :The patients were followed up 2 weeks, 4 weeks, 4 months and 6 months interval. All patients had IOP within normal limit (14-17mmHg) with medication before surgery cataract of all patients were total, fundus were invisible due to cataract. In the first post operative day (1st OPD) visual Acuity of thirty eight (38) patients (95%) were 6/24 to 6/18 and with pinhole 6/12, except 2 (two) patients (5%) among them 1 (one) (2.5%) having hyphaema. Hyphaema were relieved after 3 days by using Tab. Anaroxyl 3 times daily for 2 days and vitamin ‘C’ (250mg) daily for 15 days. After 6 weeks all patients had IOP 11mmHg to 14 mmHg without antiglaucoma medication and 39 (thirty nine) patients (95%) had achieved corrected vision 6/12 to 6/6. Except, 1 (one) (2.5%) had vision lowering counting finger 5 meter due to end stage glaucoma, who had cup disc ratio (C:D.9) 5 (five) patients (12.5%) developed polycystic bleb and rest diffuse functional bleb. Cup disc ration (C:D) of 39 (95%) was 0.4 to 0.8. no wound gap with iris proplase, thin bleb or fibrosed bleb with engorged overlying vessels were reported in any case. TAJ 2010; 23(1): 15-17